Case Report: Anal canal duplication associated with anorectal stenosis—A rare presentation - Zheng, Zhen; Xiao, Dong; Wang, Junxiang; Xu, Haozhong; Mao, Jianxiong; Wang, Xiuliang (Frontiers in Pediatrics, 2022)
Anal canal duplication is a rare gastrointestinal malformation characterized by extra anal orifices at 6 o'clock in the lithotomy position. To date, there have been only 110 reported cases. The purpose of this study is to contribute two infant cases, one of which is associated with anorectal stenosis, which has never been described.